Pelatihan Pemanfaatan Artificial Intelligences Deepseek dalam Menurunkan Plagiasi Artikel Ilmiah bagi Mahasiswa Baru - Annas, Annisa Nuraisyah; Nofirman, Nofirman; Haryanto, Abel; Machmud, Amir; Safarudin, Muhamad Sigid (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Student Creativity Program (PKM) aims to train new students in utilizing DeepSeek Artificial Intelligence (AI) as a tool to reduce plagiarism in scientific article writing. The training focuses on improving their understanding of paraphrasing, ethical citation integration, and utilizing DeepSeek's advanced features as a responsible writing assistant. The PKM implementation method is training and mentoring, consisting of three stages: (1) Presentation of conceptual material on plagiarism and writing ethics; (2) Hands-on workshops on utilizing DeepSeek for paraphrasing, idea elaboration, and draft checking; and (3) ongoing mentoring through online discussion groups. Evaluation results indicate an increase in participants' ability to produce manuscripts with greater originality. Analysis using a plagiarism checker on drafts before and after the training showed a significant decrease in indications of plagiarism, as well as an increase in participants' understanding of integrative academic writing. This program effectively empowers new students with AI literacy for responsible academic productivity.